STRATEGI PENGEMBANGAN USAHATANI BAWANG MERAH DI DESA SUNGAI GERINGGING KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR PROVINSI RIAU - Sri Ayu Kurniati (UIR Press, 2019)
Shallot plant has a good prospect to be developed if farmers have a desirability and ability to cultivate it. The purpose of this study was to identify the internal and external environment and to formulate a shallot farming development strategy. The research used a survey method located in Sungai Geringging Village, Kampar Kiri District, Kampar Regency and was selected 40 farmers as respondents. The data were analyzed using IFE, EFE and the SWOT. The results of external opportunities showed that Kampar Regency is a center for shallot cultivation, while fluctuations in the selling price of production were considered a threat factor. The use of the improved yielding seed was a strength, and a weakness was the transportation facility. The IE matrix indicated that the shallot farming is in cell III, so that it can carry out market penetration strategies and product development. The SWOT matrix showed that farming could carry out the WO (Weaknesses-Opportunities) strategy, namely with increasing optimally business capabilities related to capital loans, using applied technology through training. It requires the role of the government in accessing modern markets and increasing the ability of farmers to do business through information technology facilities and regional autonomy policies.